China, Hong Kong, and Taiwan: A Quantitative Assessment of Real and Financial Integration - Yin-Wong Cheung; Menzie D. Chinn; Eiji Fujii (Center for Economic Studies and ifo Institute (CESifo), 2003)
The status of real and financial integration of China, Hong Kong, and Taiwan is investigated using monthly data on one-month interbank rates, exchange rates, and prices. Specifically, the degree of integration is assessed based on the empirical validity of real interest parity, uncovered interest parity, and relative purchasing power parity. There is evidence these parity conditions tend to hold over longer periods, although they do not hold instantaneously. Overall, the magnitude of deviations from the parity conditions is shrinking over time. In particular, China and Hong Kong appear to have experienced significant increases in integration during the sample period. It is also found that exchange rate variability plays a major role in determining the variability of deviations from these parity conditions.
Keywords: 330; uncovered interest parity; real interest parity; purchasing power parity; exchange rates; capital mobility; market integration